Hyperbilirubinemia: a new diagnostic marker for appendicular perforation - Y. B., Ramaswami; H. S., Prakash; T. C., Raghavendra Prabhu; Jabbar, Faiyaz Abdul (International Surgery Journal, 2017)
Background: Appendicitis is one of the commonest causes of abdominal pain requiring emergency surgery. Diagnosing acute appendicitis clinically still remains a common surgical problem as the clinical signs and symptoms of other abdominal pathologic conditions mimic the diagnosis of acute appendicitis. Delay in diagnosis and surgery for this condition may lead to various complications like perforation, abdominal abscess etc. By knowing perforation prior to the exploration, we can manage the condition very effectively in terms explaining the prognosis of disease, morbidity of surgery, wound infection, and requirement of emergent nature of surgery. Aim of the study is to determine of role of hyperbilirubinemia as a new diagnostic marker to predict gangrenous/perforated appendicitis. Methods: It’s a retrospective study was conducted in the department of surgery, MMCRI, Mysore during the period of January 2015 to December 2015 total of 100 patients with clinical as well as ultrasonographic diagnosis of acute appendicitis or appendiceal perforation were made. The serum bilirubin test was carried out in all the patients pre-operatively. Results: In the study, the total 100 patients enrolled for the study, hyperbilirubinemia (> 1.2 mg/dL) in present study was found in 47 patients with 19 acute and 28 patients perforated appendicitis of all the 100 patients while 53 patients had normal bilirubin levels (≤ 1.2 mg/dL) 51 patients acute and 2 patients perforated appendix. Conclusions: Total serum bilirubin appears to be a new promising laboratory marker for diagnosing appendicular perforation. The patients with clinical signs and symptoms of appendicitis and with hyperbilirubinemia without elevation of liver enzymes should be identified as having a higher probability of appendicular perforation, suggesting total serum bilirubin levels have a predictive potential for the diagnosis of appendicular perforation.